REDESIGNING AND PROFESSIONALIZING TEACHER EDUCATION BY PILOTING ALTERNATIVES TO TRADITIONAL SUPERVISION: ADDRESSING THE CHALLENGES OF THE INDONESIAN CONTEXT - Rodgers, Adrian (International Journal of Education, 2011)
The redesign of Indonesian teacher education is moving forward at a rapid pace and Indonesianteacher educators are now in a position to augment the top down reform efforts of the nationalgovernment with redesign efforts from the ground up. Redesigning the supervision of studentteachers by addressing local problems with local solutions is one way to do this. This articleshares the redesign efforts of three teams of faculty working at universities in the United Statesand explains how these efforts might be adapted to the Indonesian context. Since local expertiseis essential in redesign efforts, it is important that Indonesian teacher educators work togetherto create a mechanism for the redesign process. The redesign of Indonesian teacher educationis moving forward at a rapid pace as unprecedented changes occur at both the national andregional levels. The size of redesign is massive because of the large population, the size andnature of the geographic area, the diversity of land and people, and the number of private andpublic schools and universities. There are a number of resources available to undertake such alarge scope of work. Teacher educators who earned Ph.D.s at home and abroad bring a rangeof expertise to the challenge and a network of quality private and public universities exist.These institutions have prepared quality elementary school teachers in the past but undernew government mandates now have additional years to prepare teachers with the hopeof enhanced preparation and teacher quality.Despite reforms mandated from the highest levels of government, some familiarchallenges confront teacher educators at the local level. Salaries for both teachers andfaculty are low and resources are stretched thin because faculty members’ teaching andservice loads are heavy. The nature of the partnership between universities and schoolsposes some challenges. Additionally, while there is international support for facultypreparation and other forms of partnership not everything that works in other countrieswill work in the same way in Indonesia because of the much larger scale of reform.Given this unique blend of large-scale reform, limited resources, and limitationson the degree to which innovations in other settings can be transferred to Indonesia,Indonesian teacher educators need to consider their role in the redesign process. Whilegovernments design reform from the top down, teacher educators need to consider how todesign change from the ground up. To undertake this work it will be helpful for Indonesianteacher educators to redesign teacher education by piloting alternatives to traditionalsupervision. Teacher educators will want to consider the role of quality supervision in thepreparation of preservice teachers and will need to consider the importance of structureand culture in the redesign process.Key words: student teacher, preservice teacher, cooperating teacher, university supervisor